An Introduction to Cosmological Models in General Relativity in Self Creation Theory of Gravitation - Nikhil Jain (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
We have presented an introduction to Cosmological Models in General Relativity in Self Creation theory of Gravitation various definitions of basic terminology is given. Many principles used in General Relativity are also explained.
Keywords: General Theory; Principle of Equivalence; Mach’s Principle; Cariolis Field; Cosmology; Cosmological Models; Vectors